Improved adhesive layer for flexible cover lenses

A silicon-containing adhesive layer with a silane-containing adhesion promoter addresses the delamination issue in foldable displays by forming a strong covalent bond, enhancing the bond strength and maintaining flexibility.

JP2025500316AActive Publication Date: 2025-01-09APPLIED MATERIALS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024537073
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-20
Publication Date
2025-01-09
Estimated Expiration
2041-12-20

AI Technical Summary

Technical Problem

Conventional methods for bonding layers of flexible cover lenses using optically clear adhesives result in delamination and increased thickness, which hinders the folding capability of foldable displays.

Method used

A silicon-containing adhesive layer with a silane-containing adhesion promoter is used to bond the hard coat layer to a thin glass substrate, forming a strong covalent bond that reduces delamination and maintains flexibility.

Benefits of technology

The silicon-containing adhesive layer with a silane-containing adhesion promoter enhances the bond strength between the hard coat and glass substrate, reducing delamination and maintaining the flexibility of foldable displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500316000001_ABST
    Figure 2025500316000001_ABST
Patent Text Reader

Abstract

An exemplary flexible cover lens and a method for its manufacture are described. The method may include exposing a surface of a substrate layer to a surface treatment plasma to form a treated surface of the substrate layer. A silicon-containing adhesive layer may be deposited on the treated surface of the substrate layer. A silane-containing adhesion promoter may be incorporated on the silicon-containing adhesive layer. The method may further include forming a hard coat layer on the silicon-containing adhesive layer, and forming the silane-containing adhesion promoter to be bonded to both the hard coat layer and the silicon-containing adhesive layer. The exemplary flexible cover lens manufactured by the method is not susceptible to folding fatigue along the bending or folding axis of the cover lens.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a flexible display cover lens having an improved adhesive layer. More particularly, the present technology relates to a flexible silicon-containing adhesive layer that bonds a substrate to a hard coat layer of a cover lens. [Background technology]

[0002] Displays for electronic devices are made possible by processes that create intricately patterned layers of material on a substrate surface. Creating patterned materials on a substrate requires controlled methods for depositing and removing the material. However, new device designs present challenges in creating high quality material layers that meet device requirements.

[0003] Thus, there is a need for improved systems and methods that can be used to create high quality devices and structures for electronic displays. The present technology addresses these and other needs. Summary of the Invention

[0004] An embodiment of the present technology includes a method for treating a flexible cover lens. The method may include exposing a surface of a substrate layer to a surface treatment plasma to form a treated surface of the substrate layer. A silicon-containing adhesive layer may be deposited on the treated surface of the substrate layer. A silane-containing adhesion promoter may be incorporated on the silicon-containing adhesive layer. The method may further include forming a hard coat layer on the silicon-containing adhesive layer, the silane-containing adhesion promoter contributing to the bond between the hard coat layer and the silicon-containing adhesive layer.

[0005] In additional embodiments, the surface treatment plasma may include oxygen and argon. In additional embodiments, the treated surface is not exposed to air before depositing the silicon-containing adhesive layer on the treated surface of the substrate layer. In further additional embodiments, the adhesive layer is deposited on the treated surface of the substrate layer by plasma-enhanced chemical vapor deposition. In further additional embodiments, the silane-containing adhesion promoter comprises a liquid sprayed or dip-coated on the silicon-containing adhesive layer. In further additional embodiments, the silane-containing adhesion promoter further comprises a methacrylate group. In further additional embodiments, forming a hard coat layer on the silicon-containing adhesive layer comprises coating a liquid hard coat polymer on the silicon-containing adhesive layer, the silicon-containing adhesive layer incorporating the silane-containing adhesion promoter. The liquid hard coat polymer coated on the silicon-containing adhesive layer is then cured to form a hard coat layer on the silicon-containing adhesive layer. In further additional embodiments, curing the liquid hard coat polymer coated on the silicon-containing adhesive layer may comprise exposing the liquid hard coat polymer to ultraviolet light.

[0006] The embodiment of the present technology further includes a flexible cover lens comprising a substrate layer and a silicon-containing adhesive layer. The adhesive layer is disposed on the substrate layer, and the adhesive layer further comprises a silicon-containing adhesion promoter. The flexible cover lens further comprises a hard coat layer disposed on the silicon-containing adhesive layer. The hard coat layer and the substrate layer are disposed on opposite sides of the silicon-containing adhesive layer, and the adhesion promoter contributes to the bonding between the hard coat layer and the silicon-containing adhesive layer.

[0007] In a further embodiment, the substrate layer is a glass layer characterized by a thickness of less than or about 50 μm. In a further embodiment, the silicon-containing adhesion layer comprises a silicon oxide layer characterized by a thickness of less than or about 1 μm. In a further embodiment, the silicon-containing adhesion promoter comprises an acryloxyalkylsilane compound. In a further embodiment, the hard coat layer comprises a urethane acrylate polymer characterized by a thickness of less than or about 50 μm. In a further embodiment, the flexible cover lens does not comprise an optically clear adhesive.

[0008] The embodiment of the present technology further includes a flexible display device structure including a light source and a flexible cover lens. The flexible cover lens is disposed on the flexible display structure, and the flexible cover lens may include a glass layer characterized by a thickness of less than or about 50 μm. The flexible cover lens further includes a silicon-containing adhesive layer disposed on the surface of the glass layer, and a hard coat layer disposed on the silicon-containing adhesive layer. The hard coat layer and the glass layer are disposed on opposite sides of the silicon-containing adhesive layer, and a silane-containing adhesion promoter contributes to the bond between the hard coat layer and the silicon-containing adhesive layer.

[0009] In a further embodiment, the silicon-containing adhesive layer comprises a silicon oxide layer. In a further embodiment, the adhesion promoter comprises an acryloxyalkylsilane compound. In yet a further embodiment, the flexible cover lens is characterized by a thickness of less than or about 100 μm. In a further embodiment, the flexible display structure further comprises a touch panel. In a further embodiment, the light source comprises a light emitting diode, an organic light emitting diode, a liquid crystal display, or a quantum dot display.

[0010] The present technology has some advantages over the conventional method of bonding the material layers of a flexible cover lens with an optically transparent adhesive.For example, an embodiment of the present technology bonds the layers of a flexible cover lens with a silicon-containing adhesive layer and a silane-containing adhesion promoter.The silane-containing adhesion promoter maintains the bonding of the layers through more bending cycles of the cover lens and other components of the foldable display.In an embodiment, the silane-containing adhesion promoter comprises at least one silane group that forms a strong bond with the silicon-containing adhesive layer and one or more additional bonding groups, such as an alkyl group, that form a bond with the organic polymer of the hard coat layer.

[0011] A further understanding of the nature and advantages of the disclosed technology may be realized by reference to the remaining portions of the specification and the drawings. [Brief description of the drawings]

[0012] [Figure 1] 1A-1D illustrate exemplary operations of a method for forming a flexible cover lens, in accordance with an embodiment of the present technology. [Figure 2A] 1 is a simplified cross-sectional view of a flexible cover lens formed in accordance with an embodiment of the present technology. [Figure 2B] 1 is a simplified cross-sectional view of a flexible cover lens formed in accordance with an embodiment of the present technology. [Figure 2C] 1 is a simplified cross-sectional view of a flexible cover lens formed in accordance with an embodiment of the present technology. [Figure 2D] 1 is a simplified cross-sectional view of a flexible cover lens formed in accordance with an embodiment of the present technology. [Diagram 3] 1 is a simplified cross-sectional view of a flexible cover lens in accordance with an additional embodiment of the present technology. [Figure 4] 1 is a simplified cross-sectional view of a flexible display device including a flexible cover lens according to an embodiment of the present technology. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Some of these figures are included as schematic diagrams. It is understood that these figures are for illustrative purposes and should not be considered to be to scale unless specifically stated to be to scale. Furthermore, as schematic diagrams, these figures are provided to aid in understanding and may not include all aspects or information as compared to realistic representations and may include exaggerated content for illustrative purposes.

[0014] In the accompanying drawings, similar components and / or features may have the same reference numbers. Additionally, various components of the same type may be distinguished by tracing the reference numbers with a letter that distinguishes between the similar components. If only a first reference number is used in this specification, the description applies to any one of the similar components having the same first reference number, regardless of the letter.

[0015] Electronic device displays typically include several layers of intricately patterned, delicate materials that work together to display high resolution images. These layers may include, among other types of layers, colorization layers to control the color of the displayed image, polarizing layers to control the polarity of the light in the displayed image, and attenuation layers to control the intensity of the light in the displayed image. A cover lens is usually placed over these layers to protect the device display from moisture, pressure, particle contamination, and scratches, among other environmental and usage hazards. The cover lens typically includes a rigid, hard surface, often made of high strength glass, that makes the layers below the display less susceptible to damage.

[0016] There is an increasing demand for electronic devices that can reversibly bend or fold their displays. For example, smartphones with foldable displays are becoming increasingly popular because they reversibly increase the screen size during use and fold to a more compact size for storage. Conventional display cover lenses made of unbending glass sheets lack the necessary folding levels, so alternative materials and designs for flexible cover lenses are sought. These alternative materials have included sheets of flexible, semi-transparent organic polymers that have the necessary folding properties. Unfortunately, many of these organic polymers are significantly softer than glass, and the surfaces of these organic polymer cover lenses are easily scratched. Many of these organic polymers also experience folding fatigue over time, producing faint, distorted lines along the folding axis in the displayed image.

[0017] Additional foldable cover lens designs include at least one ultrathin glass (UTG) layer that is significantly more flexible than conventional cover lens glass. These UTG layers can be folded with less folding fatigue, as sheets made of flexible organic polymers. However, the UTG layer is still susceptible to scratching and breaking, and a high-strength polymeric hard coat layer may be attached to the UTG layer to reduce external stress on the cover lens. Conventional methods for attaching the hard coat layer to the underlying UTG layer use a relatively thick layer of optically clear adhesive (OCA). Unfortunately, the OCA layer often delaminates from the UTG layer along the folding axis upon repeated opening and closing of the display device. The OCA layer also significantly increases the thickness of the flexible cover lens, which makes it more difficult to fold the display sufficiently.

[0018] The embodiments of the present technology solve these and other problems with flexible cover lenses having a hard coat layer bonded to a glass substrate using an optically clear adhesive. In an embodiment, a thin silicon-containing adhesive layer is used to bond the hard coat layer to the thin glass substrate of the flexible cover lens. In an additional embodiment, the silicon-containing adhesive layer comprises a thin inorganic silicon-containing layer formed on the glass substrate by a dry deposition process such as chemical vapor deposition. This deposition process creates a strong bond between the silicon-containing portion of the adhesive layer and the glass substrate. In yet an additional embodiment, the silicon-containing adhesive layer formed on the glass substrate is exposed to at least one silane-containing adhesion promoter. In an embodiment, the adhesion promoter contacts the surface of the silicon-containing adhesive layer opposite the surface that contacts the glass substrate. In an additional embodiment, the silane-containing adhesion promoter comprises at least one silane moiety operable to bond to a silicon group in the silicon-containing adhesive layer and at least one alkyl group operable to bond to a carbon group of the hard coat layer. In an embodiment, each silane-containing adhesion promoter is bonded to both the silicon-containing adhesive layer and the hard coat layer. In an additional embodiment, the bond between the adhesion promoter and the silicon-containing adhesive layer and the hardcoat layer is a covalent bond.

[0019] The strong direct bond formed by each silane-containing adhesion promoter with both the silicon-containing adhesive layer and the hard coat layer is characterized by being less susceptible to delamination than the bond between the adhesive layer and the hard coat layer using an optically clear adhesive. The thick OCA layer disposed between the adhesive layer and the hard coat layer contains fewer compounds that form direct bonds with both of these layers. In most cases, the OCA polymers bonded to each of the layers are separated by the bulk polymer of the OCA layer. This may make these layers more susceptible to delamination at the folding axis after the cover lens is repeatedly opened and closed. In contrast, the silicon-containing adhesive layer of the present technology that contains the silane-containing adhesion promoter has more direct bonds between the promoter compounds and both the silicon-containing adhesive layer and the hard coat layer, which reduces the delamination of these layers after the cover lens is repeatedly folded.

[0020] FIG. 1 illustrates exemplary operations of a method 100 for forming a flexible cover lens according to an embodiment of the present technology. The method 100 may be performed in one or more processing chambers. The method 100 may or may not include one or more operations prior to the start of the method, including deposition, etching, polishing, cleaning, or other operations that may be performed prior to the described operations. The method may include several optional operations that may or may not be explicitly related to some embodiments of the method according to the present technology. The method 100 describes operations for forming a portion of a flexible cover lens 200 shown generally in FIGS. 2A-2D, and the illustrations of FIGS. 2A-2D are described in relation to the operations of the method 100. It should be understood that FIGS. 2A-2D show only partial schematic views with limited details, and that in some embodiments, the cover lens may include any number of structural features having the aspects shown in the figures, as well as alternative structural features that may also benefit from one or more aspects of the present technology.

[0021] Method 100 may include operations for deploying the cover lens structure in a particular manufacturing operation. In some embodiments, method 100 may be performed on a base structure, while in additional embodiments, the method may be performed before or after other material formation. As shown in FIG. 3, an embodiment of the cover lens may include an intermediate set of layers 303 having reinforced adhesion disposed between a first set of layers 301 formed on a hard coat layer 312 and a second set of layers 305 on which a substrate layer 302 is formed. In yet additional embodiments, a cover lens structure including the first set of layers 301, the intermediate set of layers 303, and the second set of layers 305 may be disposed on a flexible display stack 307. A further additional embodiment of the present technology is shown in FIG. 4, which shows a cover lens 402 incorporated into an electronic display device 400 after additional processing has been completed. For example, the cover lens 402 may be incorporated into a device 400 that further includes a touch panel 410 and a light source 420, among other device features. It should be understood that device 400 may include components having any number of conductive and / or dielectric materials, including transition metals, post-transition metals, metalloids, metals including oxides, nitrides and carbides of any of these materials, and any other materials that may be incorporated within the device components.

[0022] An embodiment of the method 100 may include, in operation 102, preparing a substrate surface for depositing a silicon-containing adhesion layer. In an embodiment, operation 102 may include exposing a surface 204 of the substrate layer 202 shown in FIG. 2A to a treatment plasma. In an additional embodiment, the substrate layer 202 may be an ultra-thin glass layer exposed to a treatment plasma that removes oxidized material from the plasma-treated surface. In an additional embodiment, the treatment plasma may be formed from a reducing gas, such as hydrogen (H2) and ammonia (NH3), and a carrier gas, such as helium (He), nitrogen (N2), and argon (Ar). In yet an additional embodiment, the treatment plasma may be formed from a gas including hydrogen (H2) and argon. In additional embodiments, the treatment plasma may be characterized by a plasma temperature of greater than or about 300° C., greater than or about 325° C., greater than or about 350° C., greater than or about 375° C., greater than or about 400° C., greater than or about 425° C., greater than or about 450° C., greater than or about 475° C., greater than or about 500° C., or more. In still additional embodiments, the substrate layer 202 may be exposed to the treatment plasma for greater than or about 1 minute, greater than or about 5 minutes, greater than or about 10 minutes, greater than or about 15 minutes, greater than or about 20 minutes, greater than or about 25 minutes, greater than or about 30 minutes, greater than or about 35 minutes, greater than or about 40 minutes, greater than or about 45 minutes, greater than or about 50 minutes, or more than or about 50 minutes. In still additional embodiments, the substrate layer 202 may be an ultra-thin glass layer characterized by a thickness of less than or about 50 μm, less than or about 45 μm, less than or about 40 μm, less than or about 35 μm, less than or about 30 μm, less than or about 25 μm, less than or about 20 μm, less than or about 15 μm, less than or about 10 μm, less than or about 5 μm, or less than or equal to or less than 5 μm.

[0023] The method 100 may further include forming a silicon-containing adhesion layer 206 on the treated substrate layer 202 in operation 104. In an embodiment, the silicon-containing adhesion layer 206 may be formed by a dry deposition process. In additional embodiments, the dry deposition process may include physical vapor deposition (PVD), sputtering, chemical vapor deposition (CVD), plasma enhanced chemical vapor deposition (PECVD), high density plasma chemical vapor deposition (HDP-CVD), atomic layer deposition (ALD), or plasma enhanced atomic layer deposition (PE-ALD), among other dry deposition processes. In additional embodiments, the dry deposition process may be a PECVD process that includes exposing the treated substrate layer 202 to a deposition plasma formed from a silicon-containing gas and an oxidizing gas. In an embodiment, the silicon-containing gas may include a silane, among other silicon-containing plasma deposition gases, or may include a deposition precursor that includes silicon and carbon, such as tetraethyl orthosilicate (TEOS). In additional embodiments, the oxidizing gas may include oxygen (O2) and / or nitrous oxide (NO), among other oxidizing gases. In yet additional embodiments, the deposition plasma may further include a non-depositing carrier gas, such as helium, nitrogen (N2) and / or argon, among other carrier gases. In additional embodiments, the PECVD process deposits a silicon-containing adhesion layer 206 that includes silicon oxide. In still additional embodiments, the deposited silicon oxide material may be characterized by a mole percentage of carbon that is less than or about 5 mol%, less than or about 4 mol%, less than or about 3 mol%, less than or about 2 mol%, less than or about 1 mol%, or less than or equal to 5 mol%, less than or about 4 mol%, less than or about 3 mol%, less than or about 2 mol%, less than or about 1 mol%, or less than or equal to 1 mol%. In still additional embodiments, the deposited silicon oxide material may be characterized by a mole percentage of nitrogen that is less than or about 25 mol%, less than or about 15 mol%, less than or about 10 mol%, less than or about 5 mol%, less than or about 2 mol%, less than or about 2 mol%, or less than or about 2 mol%, or lower.

[0024] In embodiments, the silicon-containing adhesion layer 206 may be formed on the post-processing surface 204 without breaking the vacuum between the processing operation 102 and the forming operation 104. In these embodiments, the post-processing surface 204 of the substrate layer 202 is not exposed to oxidizing gases and moisture prior to forming the silicon-containing adhesion layer 206 on the post-processing surface 204. This may increase the strength of the bond between the silicon-containing adhesion layer 206 and the substrate layer 202. This may further reduce moisture and other contaminants in the deposited silicon-containing adhesion layer 206.

[0025] As shown in Figure 2A, a silicon-containing adhesion layer 206 forms on the post-processing surface 204 of the substrate layer 202. In embodiments, the silicon-containing adhesion layer 206 may be characterized by a thickness of less than or about 1000 nm, less than or about 900 nm, less than or about 800 nm, less than or about 700 nm, less than or about 600 nm, less than or about 500 nm, less than or about 400 nm, less than or about 300 nm, less than or about 200 nm, less than or about 100 nm, or less. In additional embodiments, the silicon-containing adhesion layer 206 may comprise silicon oxide, silicon oxycarbide, silicon oxynitride, silicon nitride, silicon carbide, or silicon oxycarbonitride, among other silicon-containing materials. In additional embodiments, the silicon-containing adhesive layer 206 may be characterized by a refractive index that promotes light from a light source passing through the cover lens including the adhesive layer without significant image distortion. In additional embodiments, the silicon-containing adhesive layer 206 may be characterized by a refractive index of less than or about 1.55, less than or about 1.52, less than or about 1.50, less than or about 1.48, less than or about 1.45, less than or about 1.43, less than or about 1.40, less than or about 1.38, less than or about 1.35, or lower. In yet additional embodiments, the silicon-containing adhesive layer 206 may be characterized by a hardness that prevents the cover lens from being easily scratched or dented.In embodiments, the silicon-containing adhesion layer 206 may be characterized by a hardness of greater than or about 0.1 GPa, greater than or about 0.5 GPa, greater than or about 0.5 GPa, greater than or about 1 GPa, greater than or about 1.25 GPa, greater than or about 1.25 GPa, greater than or about 1.5 GPa, greater than or about 1.75 GPa, greater than or about 2 GPa, greater than or about 2.25 GPa, greater than or about 2.5 GPa, greater than or about 2.75 GPa, greater than or about 3 GPa, greater than or about 3.25 GPa, greater than or about 3.5 GPa, or greater than or about 3.5 GPa.

[0026] Method 200 may further include forming a silane-containing adhesion promoter layer 208 on the surface of silicon-containing adhesive layer 206 or another silicon-containing layer in operation 106. As shown in FIG. 2B, silane-containing adhesion promoter layer 208 may be formed on a surface of silicon-containing adhesive layer 206 facing away from the surface of silicon-containing adhesive layer 206 that contacted treated surface 204 of substrate layer 202. In an embodiment, silane-containing adhesion promoter layer 208 may be formed on silicon-containing adhesive layer 206 by a wet method. In an additional embodiment, silane-containing adhesion promoter layer 208 may be formed by contacting a solution or vapor containing one or more silane-containing adhesion promoters with the surface of silicon-containing adhesive layer 206. In yet an additional embodiment, a solution or vapor of silane-containing adhesion promoter may be deposited on silicon-containing adhesive layer 206 by physical vapor deposition, chemical vapor deposition, vacuum deposition, spray coating, spin coating, or dip coating, among other application techniques. In additional embodiments, a silane-containing adhesion promoter layer may be formed on one or more intermediate layers between the silane-containing adhesion promoter layer 208 and the silicon-containing adhesion layer 206. In embodiments, the one or more intermediate layers may include a silicon-containing material capable of forming bonds with the silane groups in the silane-containing adhesion promoter.

[0027] In embodiments, the solution of one or more silane-containing adhesion promoters may include an aqueous solution containing an adhesion promoter in an amount of greater than or about 0.1%, greater than or about 0.2%, greater than or about 0.3%, greater than or about 0.4%, greater than or about 0.4%, greater than or about 0.5%, or more by weight. The concentration of the adhesion promoter in the aqueous solution may be relatively dilute to adjust the viscosity and surface tension of the solution to increase wetting of the adhesion promoter on the surface of the silicon-containing adhesion layer 206. In additional embodiments, the aqueous adhesion promoter solution may further include an acid to adjust the pH of the solution. In embodiments, the aqueous adhesion promoter solution may be characterized by a pH of less than or about 4.5, less than or about 4.4, less than or about 4.3, less than or about 4.2, less than or about 4.1, less than or about 4.0, less than or about 3.9, less than or about 3.8, less than or about 3.7, less than or about 3.6, less than or about 3.5, less than or about 3.4, less than or about 3.3, less than or about 3.2, less than or about 3.1, less than or about 3.0, or less. In additional embodiments, the acid may be an organic acid, such as acetic acid. Adjusting the pH of the aqueous adhesion promoter solution may increase the reactivity of the adhesion promoter with the silicon-containing adhesion layer 206.

[0028] In additional embodiments, the wet silane-containing adhesion promoter layer deposited on the silicon-containing adhesion layer 206 may be dried to form the silane-containing adhesion promoter layer 208. In embodiments, the drying process may include heating the deposited adhesion promotion layer in a dry environment characterized by a temperature of greater than or about 100° C., greater than or about 105° C., greater than or about 110° C., greater than or about 115° C., greater than or about 120° C., or greater than or equal to 120° C. In additional embodiments, the drying process may further include exposing the deposited adhesion promotion layer to a drying gas, such as dry nitrogen (N2) gas.

[0029] In an embodiment, the silane-containing adhesion promoter may be a compound that includes at least one silane moiety that bonds to a silicon atom in the silicon-containing adhesive layer 206 and at least one other moiety that bonds to the subsequently formed cured hardcoat layer 212 on the silicon-containing adhesive layer. In additional embodiments, the at least one silane moiety may include an alkylsilane group or an alkoxysilane group, among other types of silane groups. In additional embodiments, the at least one silane moiety may include a silicon (Si) atom bonded to one, two or three alkoxy groups, such as a combination of methoxy, ethoxy, acetoxy and alkoxy groups. In additional embodiments, the at least one silane moiety may be represented by the formula -Si(OR)3, where R represents an alkyl group having one to four carbon atoms. In additional embodiments, the at least one other moiety that bonds to the hardcoat layer may include one or more of an amine group, an aldehyde group, a ketone group, a carboxylic acid group, a halogen group or an alkene group, among other types of groups that react with the hardcoat layer. In yet further embodiments, the silane-containing adhesion promoter may have the formula (RO)3Si-YX, where each R independently represents an alkyl group having 1 to 4 carbon atoms, Y represents a linking group, and X represents at least one moiety operable to bond to the hardcoat layer. In yet further embodiments, the Y group may comprise an alkyl group or an alkoxy group, and at least one X group may independently be an amine group, an aldehyde group, a ketone group, a carboxylic acid group, a halogen group, or an alkene group. In yet further embodiments, the silane-containing adhesion promoter may be 3-aminopropyltriethoxysilane or methacryloxypropyltrimethoxysilane, among other silane-containing adhesion promoters.

[0030] In embodiments, a silane-containing adhesion promoter may be selected that bonds more readily to the silicon-containing adhesion layer 206 than to the substrate layer 202 made from ultra-thin glass. In additional embodiments, the treated surface 204 of the substrate layer 202 may have fewer bonding sites to which the silane moieties on the adhesion promoter bond than the silicon-containing adhesion layer 206. In these embodiments, the silicon-containing adhesion layer 206 increases the bond strength of the silane-containing adhesion promoter that bonds the silicon-containing adhesion layer to the hard coat layer. The increased bond strength makes these layers less susceptible to delamination along the folding axis of the cover lens. In additional embodiments, the silane-containing adhesion promoter may be covalently bonded to one or both of the silicon-containing adhesion layer 206 and the cured hard coat layer 212. In yet additional embodiments, the silane-containing adhesion promoter layer 208 may be characterized by the thickness of the silane-containing adhesion promoter that constitutes the silane-containing adhesion promoter layer.

[0031] The method 200 may further include, in operation 108, depositing a hard coat material 210 on the silicon-containing adhesion layer 206 including the silane-containing adhesion promoter layer 208. As shown in FIG. 2C, the hard coat material 210 may be formed on the surface of the silicon-containing adhesion layer 206 on which the silane-containing adhesion promoter layer 208 is formed. In embodiments, the hard coat material may be characterized as a liquid or gel formed by a wet process on the silicon-containing adhesion layer 206 and the silane-containing adhesion promoter layer 208. In additional embodiments, the hard coat material 210 may be deposited by a wet deposition technique such as spray coating, spin coating, or dip coating, among other wet deposition techniques.

[0032] In additional embodiments, the hard coat material 210 may include one or more acrylates, one or more sol-gels, one or more siloxanes, one or more copolymers thereof, one or more elastomers thereof, or any combination thereof. In additional embodiments, the wet hard coat material 210 includes an acrylate that may be a radiation curable acrylate, an aliphatic urethane acrylate, a copolymer thereof, an elastomer thereof, or any combination thereof, or includes an acrylate that may include a radiation curable acrylate, an aliphatic urethane acrylate, a copolymer thereof, an elastomer thereof, or any combination thereof. In yet additional embodiments, the wet hard coat material 210 includes a thermally cured acrylate and / or a UV cured acrylate. In additional embodiments, the wet hard coat material 210 includes one or more urethane-acrylates. In yet additional embodiments, the wet hard coat material 210 includes one or more urethane-acrylates having the formula:

[0033] [ka] In the above formula, R may be hydrogen or an alkyl group having 1 to 5 carbon atoms.

[0034] In additional embodiments, the wet hard coat material 210 may further optionally include one or more inorganic nanoparticles or other particulates substituted or otherwise disposed within the matrix of the hard coat material. In additional embodiments, the inorganic nanoparticles may include one or more of silica, alumina, titanium oxide, zirconium oxide, and hafnium oxide. In yet additional embodiments, the inorganic nanoparticles may be nanoparticles that may be characterized by an average particle size of less than or about 500 nm, less than or about 250 nm, less than or about 100 nm, less than or about 90 nm, less than or about 80 nm, less than or about 70 nm, less than or about 60 nm, less than or about 50 nm, or less than or equal to 50 nm. In still additional embodiments, the weight percentage of inorganic nanoparticles in the hard coat material 210 may be less than or about 75% by weight, less than or about 60% by weight, less than or about 50% by weight, less than or about 40% by weight, less than or about 30% by weight, less than or about 20% by weight, less than or about 10% by weight, less than or about 5% by weight, or lower.

[0035] In additional embodiments, one or more intermediate material layers may be disposed between the silane-containing adhesion promoter layer 208 and the wet hardcoat material 210. In embodiments, these intermediate material layers may include compounds that facilitate bonding of the hardcoat material 210 to the silane-containing adhesion promoter layer 208. In additional embodiments, these materials may include one or more compounds having chemical groups that form covalent bonds with the silane-containing adhesion promoter and one or more additional compounds that form covalent bonds with the wet hardcoat material 210.

[0036] The method 200 may further include curing the deposited hard-coat material 210 into a cured hard-coat layer 212 in operation 110. As shown in FIG. 2D, the cured hard-coat layer 212 may be disposed on a surface of the silicon-containing adhesive layer 206, which includes a silane-containing adhesion promoter layer 208. In additional embodiments, a silane-containing adhesion promoter may be covalently bonded to the cured hard-coat layer 212 and the silicon-containing adhesive layer 206 to strongly bond adjacent layers of the cover lens. In additional embodiments, the curing operation 110 may include thermal curing and ultraviolet light curing, among other curing techniques. In still additional embodiments, the deposited hard-coat material 210 may be dried prior to or as part of the curing operation 110. In embodiments, the drying process may include heating the deposited hard-coat material 210 in a dry environment. In still additional embodiments, the drying process may be performed in the same system or chamber as the drying process of the deposited silane-containing adhesion promoter layer 208.

[0037] In embodiments, the curing operation 110 may include exposing the wet or dry hardcoat material 210 to ultraviolet light. In additional embodiments, the ultraviolet light may be characterized by a peak light wavelength of less than or about 400 nm, less than or about 390 nm, less than or about 380 nm, less than or about 370 nm, less than or about 360 nm, less than or about 350 nm, less than or about 330 nm, less than or about 320 nm, less than or about 310 nm, less than or about 300 nm, or less than or equal to 400 nm. In additional embodiments, the wet or dry hardcoat material 210 may be exposed to ultraviolet light for less than or about 60 minutes, less than or about 45 minutes, less than or about 30 minutes, less than or about 15 minutes, less than or about 10 minutes, less than or about 5 minutes, less than or about 2 minutes, less than or about 1 minute, or less than or about 1 minute. In additional embodiments, terminating the curing operation 110 may fix the thickness of the cured hardcoat layer at a thickness of greater than or about 10 μm, greater than or about 20 μm, greater than or about 30 μm, greater than or about 40 μm, greater than or about 50 μm, or greater than or about 50 μm.

[0038] As noted above, the cured hardcoat layer 212 forms a strong bond with the silane-containing adhesion promoter in the silane-containing adhesion promoter layer 208. In embodiments, the bond formed by the silane-containing adhesion promoter between the cured hardcoat layer 212 and the silicon-containing adhesive layer 206 may be characterized by a peel strength that is stronger than the peel strength of a similar pair of layers bonded with an optically clear adhesive polymer. In additional embodiments, the peel strength between the cured hardcoat layer 212 and the silicon-containing adhesive layer 206 may be characterized by a 4B-5B grade based on the testing requirements of ASTM D3359.

[0039] In embodiments, the cured hard-coat layer 212 may be a layer of the cover lens that is exposed to the stresses of device use. In order for the cured hard-coat layer 212 to withstand these stresses and maintain an optically clear, scratch-free viewing surface, the layer should include high hardness characteristics and an appropriate refractive index. In embodiments where the cured hard-coat layer 212 is part of a flexible cover lens, the layer should further be characterized by excellent bending properties, low bending fatigue, and excellent light transmission. In embodiments, the cured hard-coat layer 212 may be characterized by a pencil hardness of greater than or about 2H, greater than or about 3H, greater than or about 4H, greater than or about 5H, greater than or about 6H, greater than or about 7H, greater than or about 8H, greater than or about 9H, or greater than or about 9H. In additional embodiments, the cured hardcoat layer 212 may be characterized by a nano-indentation hardness of greater than or about 0.1 GPa, greater than or about 0.5 GPa, greater than or about 0.5 GPa, greater than or about 1 GPa, greater than or about 1.25 GPa, greater than or about 1.25 GPa, greater than or about 1.5 GPa, greater than or about 2 GPa, greater than or about 2.5 GPa, greater than or about 3 GPa, greater than or about 3.5 GPa, greater than or about 4 GPa, greater than or about 4.5 GPa, greater than or about 5 GPa, or even greater. In still additional embodiments, the cured hardcoat layer 212 may be characterized by a refractive index of less than or about 1.55, less than or about 1.52, less than or about 1.52, less than or about 1.50, less than or about 1.48, less than or about 1.45, less than or about 1.43, less than or about 1.40, less than or about 1.38, less than or about 1.35, or lower.

[0040] In additional embodiments, the cured hardcoat layer 212 may be characterized by a bending inside radius of less than or about 20 mm, less than or about 15 mm, less than or about 10 mm, less than or about 7.5 mm, less than or about 5 mm, less than or about 2.5 mm, less than or about 1 mm, or less than or equal to 1. In additional embodiments, the cured hardcoat layer 212 may be characterized by a light transmittance of greater than or about 90%, greater than or about 95%, greater than or about 96%, greater than or about 97%, greater than or about 98%, greater than or about 99%, or greater than or about 99%, in the visible portion of the spectrum (e.g., wavelengths from about 400 nm to about 700 nm). In still additional embodiments, the flexible cover lens 200 including the cured hard coat layer 212 may be characterized by a critical strain of less than or about 15%, less than or about 14%, less than or about 13%, less than or about 12%, less than or about 11%, less than or about 10%, less than or about 9%, less than or about 8%, less than or about 7%, less than or about 6%, less than or about 5%, or less than or equal to 15%.

[0041] FIG. 3 shows another embodiment of the present technology, in which the substrate layer 302, the silicon-containing adhesion layer 306, the silane-containing accelerator 308 and the hard coat layer 312 are at least part of the intermediate set of layers 303 disposed between the first set of layers 301 facing the viewer and the second set of layers facing the flexible display stack 307. The first set of layers 301 disposed on the intermediate set of layers 303 may include one or more layers such as an additional adhesion promoter layer, an anti-reflection layer, an additional hard coat layer and an anti-fingerprint layer, among other layers. The second set of layers 305 disposed below the intermediate layer 303 may include one or more layers such as a moisture barrier layer, an impact absorbing layer and a glass layer, among other layers. In an embodiment, the cover lens includes the first set of layers 301, the intermediate set of layers 303 and the second set of layers 305. In additional embodiments, these layers of cover lenses may be disposed above the flexible display stack 307.

[0042] In an embodiment, the first set of layers 301 may include one or more adhesion promoting layers disposed on the hard coat layer 312. In an additional embodiment, the adhesion promoting layer may include one or more of silicon oxide, silicon carbide, silicon oxycarbide, silicon nitride, silicon oxynitride, and silicon oxycarbonitride. In an additional embodiment, the adhesion promoting layer may be characterized by a carbon concentration gradient along the thickness of the layer. In yet an additional embodiment, the surface of the adhesion promoting layer closer to or in contact with the hard coat layer 312 may be characterized by a higher carbon concentration than the surface facing away from the adhesion promoting layer. In an embodiment, the adhesion promoting layer may be characterized by a carbon concentration of greater than or about 1%, greater than or about 2.5%, greater than or about 5%, greater than or about 7.5%, greater than or about 10%, or more by weight. In still additional embodiments, the adhesion promoting layer may be characterized by a thickness of greater than or about 0.01 μm, greater than or about 0.01 μm, greater than or about 0.05 μm, greater than or about 0.1 μm, greater than or about 0.25 μm, greater than or about 0.5 μm, greater than or about 0.75 μm, greater than or about 1 μm, greater than or about 2 μm, greater than or about 5 μm, greater than or about 10 μm, greater than or about 25 μm, greater than or about 50 μm, or more.

[0043] In yet further additional embodiments, the first set of layers 301 may include an anti-reflective layer that reduces or prevents light reflection from the surface of the cover lens. In embodiments, the anti-reflective layer may include one or more silicon-containing materials, such as silicon nitride, silicon oxynitride, silicon carbonitride, and silicon oxycarbonitride, among other silicon-containing materials. In additional embodiments, the anti-reflective layer may be characterized by a refractive index of greater than or about 1.5, greater than or about 1.6, greater than or about 1.7, greater than or about 1.7, greater than or about 1.8, greater than or about 1.9, greater than or about 2.0, greater than or about 2.1, greater than or about 2.2, greater than or about 2.3, greater than or about 2.4, greater than or about 2.5, or greater than or equal to 2.5. In still additional embodiments, the antireflective layer may be characterized by an optical transmittance in the visible range of greater than or about 85%, greater than or about 90%, greater than or about 95%, greater than or about 97.5%, greater than or about 99%, or greater than or about 99%. In additional embodiments, the antireflective layer may be characterized by a thickness of less than or about 1000 nm, less than or about 500 nm, less than or about 250 nm, less than or about 100 nm, less than or about 50 nm, less than or about 40 nm, less than or about 30 nm, less than or about 20 nm, less than or about 10 nm, less than or about 5 nm, less than or about 1 nm, or less than or about 1 nm.

[0044] In additional embodiments, the first set of layers 301 may further include one or more dry hard-coat layers. In embodiments, the dry hard-coat layer is characterized as dry because it is formed by one or more types of vapor deposition processes. After being deposited or otherwise formed, the dry hard-coat layer may be a completely dry or substantially dry solid layer. The dry hard-coat layer may be, or may be deposited, formed, or otherwise produced by a vapor deposition process that may include PVD, CVD, PE-CVD, HDP-CVD, ALD, PE-ALD, other vacuum or vapor deposition processes, or any combination thereof. In some examples, the dry hard-coat layer may be generated, deposited, coated, or otherwise formed by vacuum processing, atmospheric processing, solution processing, or other deposition or coating techniques, and then optionally treated or cured by exposure to heat and / or UV. In one or more embodiments, the dry hard-coat layer may be formed, treated, and / or otherwise processed on a sheet-to-sheet or roll-to-roll processing system. For example, the dry hard-coat layer may be deposited, coated, or otherwise formed on an underlying surface, layer, or device by one or more sheet-to-sheet or roll-to-roll process techniques. In still additional embodiments, the dry hardcoat layer may be characterized by a porosity of less than or about 10 vol.%, less than or about 9 vol.%, less than or about 8 vol.%, less than or about 7 vol.%, less than or about 6 vol.%, less than or about 5 vol.%, less than or about 4 vol.%, less than or about 3 vol.%, less than or about 2 vol.%, less than or about 1 vol.%, or less than or equal to 10 vol.%.In still additional embodiments, the dry hardcoat layer may be characterized by an inside bending radius of about 1 mm to about 5 mm, a bending outside radius of less than or about 20 mm, less than or about 15 mm, less than or about 10 mm, less than or about 5 mm, or even less.

[0045] In additional embodiments, the first set of layers 301 may further include an anti-fingerprint layer as a top layer of the flexible cover lens. The anti-fingerprint layer, also known as an anti-soiling layer, may include one or more layers, films or coatings and provides the top surface of the entire flexible cover lens. The anti-fingerprint layer reduces or prevents fingerprints, smudges, scratches and other contaminants on the outer and / or top surface of the layer. The anti-fingerprint layer may include one or more materials that may be or include fluorosilanes, perfluoropolyether-containing silane polymers, chlorosilanes, oxysilanes, fluoroethylene, perfluoropolyethers, fluorinated nitrogen or nitrogen-fluorine containing compounds, polymers thereof, dopants thereof, or any combination thereof.

[0046] In an embodiment, the second set of layers 305 may include a moisture barrier layer. In additional embodiments, the moisture barrier layer may be one or more membranes, coatings, or other layers that have inherent moisture or water resistant properties and are bendable, flexible, and / or foldable. In yet additional embodiments, the moisture barrier layer may include one or more layers, such as a moisture and / or water resistant vapor layer, a high surface energy layer (e.g., hydrophilic properties), a planarization layer, an encapsulation layer, portions of these layers, or combinations thereof. In one or more embodiments, the moisture barrier layer may include one or more materials that may be or include silicon oxide, silicon nitride, silicon oxynitride, dopants thereof, or any combination thereof. In additional embodiments, the moisture barrier layer may include a single layer, while in further additional embodiments, the moisture barrier layer may include multiple sublayers, such as 2, 3, 4, 5, 6, 7, 8, 9, or 10 or more sublayers. In embodiments, the moisture barrier layer may include multiple sublayers included in the moisture barrier layer, such as more than or about 2 sublayers, more than or about 3 sublayers, more than or about 4 sublayers, more than or about 5 sublayers, or more sublayers. In further additional embodiments, the moisture barrier layer may include a membrane stack having three or more sublayers, such as a first sublayer, a second sublayer, and a third sublayer, where the second sublayer is disposed between the first sublayer and the second sublayer. In an embodiment, the membrane stack may be a SiN / SiO / SiN stack, where the first sublayer may be or may include silicon nitride, the second sublayer may be or may include silicon oxide, and the third sublayer includes silicon nitride. In an embodiment, the moisture barrier layer is 10 g / m 2 Less than 1 day or about 10g / m 2 day, 5g / m 2 Less than a day or about 5g / m 2 day, 1g / m 2 Less than a day or about 1g / m 2 day, 0.5g / m 2 Less than a day or about 0.5 g / m2 day, 0.1g / m 2 Less than a day or about 0.1 g / m 2 day, 0.01g / m 2 Less than a day or about 0.01 g / m 2 day, 0.1g / m 2 Less than a day or about 0.1 g / m 2 day, 0.1g / m 2 Less than a day or about 0.1 g / m 2 day, 0.01g / m 2 Less than a day or about 0.01 g / m 2 day, 0.001g / m 2 Less than a day or about 0.001 g / m 2 day, 0.0001g / m 2 Less than 1 day or about 0.0001g / m 2 day, 0.00001g / m 2 Less than 1 day or about 0.00001g / m 2 day, 0.000001g / m 2 Less than a day or about 0.000001g / m 2 The composition may be characterized by a water vapor transport rate of 100-250 nm or less.

[0047] In additional embodiments, the second set of layers 305 may include an impact absorbing layer. In additional embodiments, the impact absorbing layer may include one or more layers that are bendable, flexible, and / or foldable and are used to absorb vibration or impact. In additional embodiments, the impact absorbing layer may include one or more materials that may be or include ether urethane, ester urethane, aliphatic urethane, aliphatic polyurethane, aliphatic polyester urethane, thermosetting polysulfide, polyamide, copolymers thereof, elastomers thereof, or any combination thereof. In additional embodiments, the impact absorbing layer may be characterized by a thickness of less than or about 250 μm, less than or about 200 μm, less than or about 150 μm, less than or about 100 μm, less than or about 50 μm, less than or about 25 μm, less than or about 10 μm, or less than or equal to 10 μm. In yet additional embodiments, the impact absorbing layer may include an elastomeric layer having a thickness of less than or about 100 μm, less than or about 75 μm, or less than or equal to 100 μm.

[0048] In yet additional embodiments, the second set of layers 305 may include a glass layer. In additional embodiments, a surface of this glass layer may be in contact with the flexible display stack 307. In additional embodiments, the glass layer may be an optically clear or transparent glass layer characterized by a thickness of less than or about 200 μm, less than or about 150 μm, less than or about 100 μm, less than or about 90 μm, less than or about 80 μm, less than or about 70 μm, less than or about 60 μm, less than or about 50 μm, less than or about 40 μm, less than or about 30 μm, less than or about 20 μm, less than or about 10 μm, or less than or equal to or less than 10 μm.

[0049] Method 200 may further include, at operation 112, incorporating a cover lens including substrate layer 202, silicon-containing adhesive layer 206, and cured hardcoat layer 212 into an electronic display. Figure 4 shows a simplified schematic cross-sectional view of an electronic display 400 including a cover lens 402 disposed over an assembly of additional elements within the electronic display according to an embodiment of the present technology. These additional elements may include contrast enhancement and / or polarizer layer 404, touch panel 406, display layer 408 including a light source (not shown), substrate layer 410, and backing film 412. These layers may collectively create a bendable or foldable electronic display for electronic devices such as smartphones, monitors, televisions, tablets, laptop computers, or watches, among other types of electronic devices.

[0050] In an embodiment, the contrast enhancement and / or polarizer layer 404 may include a multi-functional film layer including a polarizer film. In an additional embodiment, the contrast enhancement and / or polarizer layer 404 may be used to reduce unwanted reflections from reflective metals forming the electrode lines or metal structures in the electronic display 400. In yet an additional embodiment, the contrast enhancement and / or polarizer layer 404 may include a quarter wave retarder and a linear polarizer formed from a flexible lens film having a thickness of less than or about 0.2 mm.

[0051] In additional embodiments, the touch panel 406 may include a touch sensor IC board and a touch sensor (not shown). In additional embodiments, the touch sensor IC board is a metal-based flexible printed circuit board. In further additional embodiments, the display layer 408 may include one or more light emitting diode (LED) displays, one or more liquid crystal displays (LCDs) or other suitable display devices. In additional embodiments, the display layer 408 may include an organic light emitting diode (OLED) display. In further additional embodiments, the display layer 408 may include a quantum dot (OD) display. In additional embodiments, the display layer 408 may include a thin film encapsulation (TFE), an organic light emitting layer, a driver IC board, and thin film transistors (TFTs).

[0052] In additional embodiments, the substrate layer 410 may include a flexible substrate made of plastic or polymer. In embodiments, the substrate layer 410 may be transparent and / or colorless, and in some examples may be conductive. The substrate layer 410 may include one or more polyimide materials, polyester terephthalate, polyether ether ketone, transparent conductive polyester, polycarbonate, polyaryl ether ketone, or any combination thereof. In additional embodiments, the backing film 412 may include one or more heat sink layers and / or one or more protective barrier layers.

[0053] An embodiment of the present technology includes a method for producing a flexible cover lens with reduced bending and folding fatigue, which is due in part to a silicon-containing adhesive layer that makes the cover lens less susceptible to distortion and delamination. In an embodiment, the silicon-containing adhesive layer includes a silane-containing adhesion promoter that facilitates strong bonding between the adhesive layer and a hard coat layer that protects the underlying components of the display from environmental stresses and normal wear and tear. In an additional embodiment, a silicon-containing adhesive layer that includes a silane-containing adhesion promoter is used instead of a conventional optically transparent adhesive that is characterized by weak bonding between the hard coat layer of the flexible cover lens and the layer below it, such as between the hard coat layer and an ultra-thin glass substrate layer.

[0054] In the foregoing description, for purposes of explanation, numerous details are set forth in order to provide an understanding of various embodiments of the present technology. However, it will be apparent to one skilled in the art that certain embodiments may be practiced without some of these details or with additional details.

[0055] Although several embodiments have been disclosed, those skilled in the art will recognize that various modifications, alternative structures, and equivalents can be used without departing from the spirit of the embodiments. Moreover, some well-known processes and elements have not been described to avoid unnecessarily obscuring the present technology. Thus, the above description should not be taken as limiting the scope of the present technology. Furthermore, although a method or process may be described sequentially or as steps, it should be understood that the operations may be performed simultaneously or in an order different from that described.

[0056] Where a range of values ​​is provided, unless otherwise clear from the context, each intervening value between the upper and lower limits of that range is understood to be specifically disclosed, to the smallest fraction of the unit of the lower limit. Narrower ranges between any stated or intervening value in a stated range and any other stated or intervening value in that stated range are also encompassed. The upper and lower limits of those smaller ranges may be independently included or excluded from the range, and each range in which either limit is included, neither limit is included, or both limits are included in the technology, subject to the specifically excluded limits of the stated range. If the stated range includes one or both of these limits, then ranges excluding either or both of those included limits are also included.

[0057] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly indicates otherwise. Thus, for example, reference to "an adhesion promoter" includes a plurality of such promoters, reference to "the layer" includes reference to one or more layers and equivalents thereof known to those skilled in the art, and so forth.

[0058] Furthermore, as used in this specification and the claims that follow, the words "comprise(s)", "comprising", "contain(s)", "containing", "include(s)" and "including" are intended to specify the presence of stated features, integers, components or operations, but they do not exclude the presence or addition of one or more other features, integers, components, operations, acts or groups.

Claims

1. exposing a surface of a substrate layer to a surface treatment plasma to form a treated surface of the substrate layer; depositing a silicon-containing adhesion layer on the treated surface of the substrate layer; incorporating a silane-containing adhesion promoter onto said silicon-containing adhesive layer; forming a hardcoat layer on the silicon-containing adhesive layer, the silane-containing adhesion promoter bonding to both the hardcoat layer and the silicon-containing adhesive layer; A method for treating a flexible cover lens comprising:

2. 10. The flexible cover lens treatment method of claim 1, wherein the surface treatment plasma comprises oxygen and argon.

3. 10. The flexible cover lens treatment method of claim 1, wherein the treated surface of the substrate layer is not exposed to air prior to the depositing of the silicon-containing adhesion layer onto the treated surface.

4. 10. The flexible cover lens treatment method of claim 1, wherein the silicon-containing adhesion layer is deposited on the treated surface of the substrate layer by plasma enhanced chemical vapor deposition.

5. 10. The flexible cover lens treatment method of claim 1, wherein the silane-containing adhesion promoter comprises a liquid that is sprayed or dip-coated onto the silicon-containing adhesive layer.

6. The flexible cover lens treatment method of claim 1 , wherein the silane-containing adhesion promoter further comprises a methacrylate group.

7. The forming of the hard coat layer on the silicon-containing adhesive layer comprises: coating a liquid hard coat polymer onto the silicon-containing adhesive layer, the silane-containing adhesion promoter being incorporated onto the silicon-containing adhesive layer; Curing the liquid hard coat polymer coated on the silicon-containing adhesive layer to form the hard coat layer on the silicon-containing adhesive layer; The method of claim 1 comprising:

8. 8. The flexible cover lens treating method of claim 7, wherein the curing the liquid hard-coat polymer coated on the silicon-containing adhesive layer further comprises exposing the liquid hard-coat polymer to ultraviolet light.

9. A substrate layer; a silicon-containing adhesion layer in contact with a surface of the substrate layer, the silicon-containing adhesion layer comprising a silicon-containing adhesion promoter; a hard coat layer on the silicon-containing adhesive layer, the hard coat layer and the substrate layer being disposed on opposite sides of the silicon-containing adhesive layer, and the silicon-containing adhesion promoter being bonded to the hard coat layer and the silicon-containing adhesive layer; A flexible cover lens comprising:

10. 10. The flexible cover lens of claim 9, wherein the substrate layer comprises a glass layer characterized by a thickness of less than or about 50 μm.

11. 10. The flexible cover lens of claim 9, wherein the silicon-containing adhesive layer comprises a silicon oxide layer characterized by a thickness of less than or about 1 μm.

12. 10. The flexible cover lens of claim 9, wherein the silicon-containing adhesion promoter comprises an acryloxyalkylsilane compound.

13. 10. The flexible cover lens of claim 9, wherein the hard coat layer comprises a urethane acrylate polymer characterized by a thickness of less than or about 50 μm.

14. 10. The flexible cover lens of claim 9 which is free of optically clear adhesives.

15. a flexible display structure including a light source; a flexible cover lens disposed on the flexible display structure; Equipped with The flexible cover lens is a glass layer characterized by a thickness of less than or about 50 μm; a silicon-containing adhesion layer on a surface of the glass layer; a hard coat layer on the silicon-containing adhesive layer, the hard coat layer and the glass layer being disposed on opposite sides of the silicon-containing adhesive layer, and a silane-containing adhesion promoter contributing to bonding the hard coat layer to the silicon-containing adhesive layer; A flexible display device comprising:

16. 16. The flexible display device of claim 15, wherein the silicon-containing adhesive layer comprises a silicon oxide layer.

17. 16. The flexible display device of claim 15, wherein the silicon-containing adhesion promoter comprises an acryloxyalkylsilane compound.

18. 16. The flexible display device of claim 15, wherein the flexible cover lens is characterized by a thickness of less than or about 100 μm.

19. 16. The flexible display device of claim 15, wherein the flexible display structure further comprises a touch panel.

20. 16. The flexible display device of claim 15, wherein the light source comprises a light emitting diode, an organic light emitting diode, a liquid crystal display, or a quantum dot display.

Citation Information

Patent Citations

  • Coated, chemically strengthened, thin, flexible glass

    JP2017529305A

  • Article with water repellent oil repellent layer and manufacturing method therefor

    JP2019116097A

  • Protective display film containing glass

    JP2019532356A

  • Laminate

    WO2017030046A1

  • Thin flexible glass cover with a fragment retention hard coating

    WO2021026408A1